CFD‐Modellierung von Nasselektroabscheidern mit koaxial angeordneten Draht‐und Rohrelektroden. Issue 3 (13th December 2012) - Kaiser, Sven; Walzel, Peter; Fahlenkamp, Hans
<x xml:space="preserve">Abstract</x> The design of electrostatic precipitators is very complex, especially if the intended operational conditions are characterized by the presence of a very high load of particles or droplets. In this case the high amount of particle bounded charge leads to a significant disturbance of the corona development causing a deterioration of precipitation efficiency. This effect is known as corona quenching. The objective of this work is the development of a numerical model based on computational fluid dynamics and capable to cover this working range.